Fabrication, characterization, and potential applications of re-assembled casein micelles - Khan, Muhammed Aslam; Hemar, Yacine; Li, Jiecheng; Yang, Zhi; De Leon-Rodriguez, Luis M. (Critical reviews in food science and nutrition, 2024)
Re-assembled casein micelles (rCMs), were formulated in the 1970s as a model system to understand native casein micelles (nCMs) in milk. These early works allowed an understanding of the critical factors involved in the formation of rCMs, such as minerals (citrate, phosphate, and calcium), casein type (α s -, β-, and κ-casein) and the extent of their phosphorylation. rCMs were also used to understand the effect of treatments such as ethanol, high hydrostatic pressure and heating on the stability and integrity of the micelles. More recently, the applications of rCMs have been investigated, these include their use as a nanocarrier of bioactive molecules and as electrode-bound substrates to monitor chymosin activity by electrochemistry, to cite a few. Moreover, the potential to use rCMs in both food and non-food applications remains to be fully exploited. The advantage of choosing rCMs over nCMs as an encapsulant and a lucrative food ingredient is due to their more efficient preparation and being free from impurities. In this review, we report on the formulation of rCMs, their physico-chemical properties and their behavior under different physico-chemical treatments, along with the applications and challenges of rCMs in food systems and their industrial production as a dairy ingredient.